Applicability of an empirical law to predict significant sea-wave heights from microseisms along the Western Ligurian Coast (Italy). (1st July 2016) - Ferretti, Gabriele; Scafidi, Davide; Cutroneo, Laura; Gallino, Stefano; Capello, Marco
Abstract: The use of microseisms with appropriate predictive laws is a reliable method for estimating such sea-wave parameters as period and significant height. Through the use of opportune predictive laws calibrated with measurements obtained from wave buoys, it is possible to determine the significant height of the wave as a function of the spectral energy-content of the microseism. In this paper we will present a procedure that utilises microseisms recorded by a micro network of five seismic stations to predict the significant height of waves, and its uncertainty, along the western Ligurian coast (Italy). The calibration and validation of the procedure was performed using wave measurements obtained from a wave buoy off Capo Mele (Imperia, Italy) over a two and a half year period. The differences between the significant heights measured by the wave buoy and the empirical predictions were less than 10 cm (corresponding to 10% of the mean measured value) for 47% of the data and less than 20 cm (corresponding to 20% of the mean measured value) for 72%. Highlights: Microseisms were used to predict significant sea-wave heights. An empirical predictive law was calibrated and applied to the Ligurian Sea (Italy). Data from the wave buoy off Capo Mele were used to verify the empirical law. 70% of the predicted wave heights varied from the measured ones by less than 20 cm.